Seasonal variability of eddy kinetic energy in a global high‐resolution ocean model. Issue 21 (11th November 2015) - Rieck, Jan K.; Böning, Claus W.; Greatbatch, Richard J.; Scheinert, Markus
Abstract: A global ocean model with 1/12° horizontal resolution is used to assess the seasonal cycle of surface eddy kinetic energy (EKE). The model reproduces the salient features of the observed mean surface EKE, including amplitude and phase of its seasonal cycle in most parts of the ocean. In all subtropical gyres of the Pacific and Atlantic, EKE peaks in summer down to a depth of ∼350 m, below which the seasonal cycle is weak. Investigation of the possible driving mechanisms reveals the seasonal changes in the thermal interactions with the atmosphere to be the most likely cause of the summer maximum of EKE. The development of the seasonal thermocline in spring and summer is accompanied by stronger mesoscale variations in the horizontal temperature gradients near the surface which corresponds, by thermal wind balance, to an intensification of mesoscale velocity anomalies toward the surface. Key Points: Surface eddy kinetic energy is realistically simulated in a high‐resolution ocean model Annual cycle of eddy kinetic energy peaks in summer in all subtropical gyres Mesoscale thermal wind balance drives annual cycle of surface eddy kinetic energy